The Leadership of Academic Administrators Affected Personnels Administration in the Schools under the Sisaket Primary Educational Service Area Office 1 - Jamlong, Watcharaporn; Khattiyasuwan, Saksit; Suriyasookprasert, Pichai; Wisetsri, Suphap; Suriyasookprasert, Supaporn (Rajapark Journal, 2024)
The purposes of this research were: 1) to study the leadership of educational institution administrators under the jurisdiction of the Sisaket Primary Educational Service Area Office 1; 2) Study personnel management in educational institutions under the jurisdiction of Sisaket Primary Educational Service Area Office 1, and 3) study the leadership of educational institution administrators that affects personnel management in educational institutions, under the jurisdiction of Sisaket Primary Educational Service Area Office 1. It is descriptive research. The sample consisted of 310 school administrators and teachers. The sample size was determined using multi-stage random sampling and drawing lots to complete the number in the specified proportion. The instrument used is a questionnaire regarding the opinions of executives’ leadership according to the concepts of Kuss and Posner and personnel management in educational institutions, according to Flippo’s concept. Statistics used include mean, standard deviation, and stepwise multiple regression. The results of the research found that 1) the overall leadership of educational institution administrators under the jurisdiction of Sisaket Primary Educational Service Area Office 1 is at a high level. 2) Personnel management in educational institutions, under the jurisdiction of Sisaket Primary Educational Service Area Office 1, the overall level is high. And 3) The leadership of school administrators includes the power of personnel. The forecast for personnel management in educational institutions was 45 percent.